Kegagalan nazir dalam tata kelola dan akuntabilitas pada kebangkrutan pondok pesantren - Mahroji, Mahroji; Melzatia, Shinta; Rachmaini , Nurul (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the bankruptcy of Islamic boarding schools financed by waqf funds. The research was conducted using a case study method at one of the pesantren that stopped operating in the Banten Province, with interview and observation techniques. Several factors determine the sustainability of waqf, namely the capability of human resources, intensification of entrepreneurial financing programs, strengthening of supporting infrastructure, and good governance. The results show that the sustainability of a pesantren is not only determined by the continuous support of waqf funds from the wakif. However, pesantren as nazir must also have the ability to manage the waqf property so that the waqf property can develop. The bankruptcy of Islamic boarding schools is caused by the failure of Islamic boarding schools in terms of human resources. They are not following their competencies, do not have a business, investment, and financial capabilities, apart from the ability in education, which is the core business of pesantren; and aspects of poor pesantren governance.